(untitled) (Research, Society and Development, 2021)
The aim of this study is to analyze the impact of technological imposition on remote classes in the Covid-19 pandemic, as well as describing the role of the Internet in the realization of this modality of classes. The main question of study is established - to what extent technological imposition affects the professional practice of teachers, and in order to answer it, a non-systematic literature review was carried out, which provided subsidies that indicate the impact, not only the way it was imposed was harmful to both professional practice but also the teachers’ health, who were forced to reinvent themselves professionally, and being charged with expertise and techniques they did not have. It is cautioned that the indiscriminate use of technology should not be seen as a solution to all educational problems, and its use in a responsible manner is recommended. Therefore, it is concluded that the technological imposition due to the pandemic was harmful to professional practice, and especially the teachers’ health. Finally, the fundamental study studies future empirical studies, with the active participation of teachers.